The influence of the brazilian public school math olympiad on the basic education development index: an analysis in the municipality of Coruripe-Alagoas (International Seven Journal of Multidisciplinary, 2023)
This article aims to analyze the influence of the Brazilian Mathematics Olympiad for Public and Private Schools (OBMEP) on the Basic Education Index (IDEB) in a municipality of Alagoas in the period from 2007 to 2017. It was developed from the collection and analysis of data through interviews and semi-structured questionnaires prepared by the proponents themselves, and directed to the coordinators of the aforementioned municipality, in order to analyze the influence of the Brazilian Mathematics Olympiad for Public Schools on the IDEB results. Based on the data obtained, it was clear that since the insertion of programs aimed at improving student performance in the OBMEP, the results of the IDEB of the municipality were also improved, reaching 6.3 points in 2017, which means an increase of 1.9 points compared to 2015.